31 students of the 3rd Cohort of the BJTU–UMPSA Dual Degree Programme celebrated in a simple ceremony at KLIA - Naqiah, Puaad (UMPSA, 2024)
SEPANG, 20 September 2024 – A mix of emotions—sadness, joy, and various reactions—was evident on the faces of students and parents as they bid farewell to 31 students of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), who are set to continue their studies for another two and a half years at Beijing Jiaotong University (BJTU) as part of the UMPSA–BJTU Dual Degree Programme.